PENGARUH PROFESIONALISME AUDITOR TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS DALAM PROSES PENGAUDITAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA AUDITOR DI KAP SUMATERA) - Rahmad Budi Raharjo; Kamaliah '; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted to prove that the variable-vartiabel professionalism of auditors that is dedication to the profession, social obligations, independence, trust and professional relationships among members peofesi antas are either partially or simultaneously affect the level of materiality of the independent auditor's report. Then the population of this study is the auditors who work in accounting firms in Sumatra. Samples were taken by 19 KAP adal believe Padang in Sumatra, Pekanbaru and Medan. Samples taken are auditors who worked on the KAP. The method used in the selection of the sample is purposive sampling. In this study include the auditor follows the hierarchy based on the level of the internship, the staff junior / senior, supervisor / manager and partner.Analysis of the data in this study using multiple linear regression statistical methods, namely statistical methods aimed at testing between more than one independent variable on the dependent variable. Hypothesis testing is used first to fifth hipotesais t test. Where the test aimed to see the effect of independent variables (independent variables) on the dependent variable (the dependent variable) partially. While hypothesis testing is used to test six F. This test aims to see the effect of independent variables simultaneously (simultaneously) on the dependent variable.Based on the research results, it was concluded that that the devotion to the profession, social obligations and independence has no significant effect partially terdapap materiality level audit reports, while belief in the profession and variables with fellow members of the profession have a significant influence on the level of materiality secrara partial audit report. Furthermore, this study also shows that all the independent variables (devotion to the profession, social obligations, independence, confidence profession relationships with fellow colleagues) jointly influence the dependent variable (the level of materiality).Keywords: Level of Materiality, Auditor Professionalism